Effect of whole-plant corn silage treated with lignocellulose-degrading bacteria on growth performance, rumen fermentation, and rumen microflora in sheep - W. Guo; X.J. Guo; L.N. Xu; L.W. Shao; B.C. Zhu; H. Liu; Y.J. Wang; K.Y. Gao (Animal, 2022)
Lignification of cellulose limits the effective utilisation of fibre in plant cell wall. Lignocellulose-degrading bacteria secrete enzymes that decompose lignin and have the potential to improve fibre digestibility. Therefore, this study aimed to investigate the effect of whole-plant corn silage inoculated with lignocellulose-degrading bacteria on the growth performance, rumen fermentation, and rumen microbiome in sheep. Twelve 2-month-old male hybrid sheep (Dorper ♂ × small-tailed Han ♀) were randomly assigned into two dietary groups (n = 6): (1) untreated whole-plant corn silage (WPCS) and (2) WPCS inoculated with bacterial inoculant (WPCSB). Whole-plant corn silage inoculated with bacterial inoculant had higher in situ NDF digestibility than WPCS. Sheep in the WPCSB group had significantly higher average daily gain, DM intake, and feed conversion rate than those in the WPCS group (P < 0.05). Furthermore, higher volatile fatty acid concentrations were detected in WPCSB rumen samples, leading to lower ruminal pH (P < 0.05). The WPCSB group showed higher abundance of Bacteroidetes and lower abundance of Firmicutes in the rumen microbiome than the WPCS group (P < 0.05). Multiple differential genera were identified, with Prevotella being the most dominant genus and more abundant in WPCSB samples. Moreover, the enriched functional attributes, including those associated with glycolysis/gluconeogenesis and citrate cycle, were more actively expressed in the WPCSB samples than in the WPCS samples. Additionally, certain glucoside hydrolases that hydrolyse the side chains of hemicelluloses and pectins were also actively expressed in the WPCSB microbiome. These findings suggested that WPCSB increased NDF digestibility in three ways: (1) by increasing the relative abundance of the most abundant genera, (2) by recruiting more functional features involved in glycolysis/gluconeogenesis and citrate cycle pathways, and (3) by increasing the relative abundance and/or expression activity of the glucoside hydrolases involved in hemicellulose and pectin metabolism. Our findings provide novel insights into the microbial mechanisms underlying improvement in the growth performance of sheep/ruminants. However, the biological mechanisms cannot be fully elucidated using only metagenomics tools; therefore, a combined multi-omics approach will be used in subsequent studies.